Genetic Diversity and Relatedness of Sweet Cherry (Prunus Avium L.) Cultivars Based on Single Nucleotide Polymorphic Markers - Fernandez i Marti, Angel; Athanson, Blessing; Koepke, Tyson; Font i Forcada, Caroline; Dhingra, Amit; Oraguzie, Nnadozie (Frontiers in Plant Science, 2012)
Most previous studies on genetic fingerprinting and cultivar relatedness in sweet cherry were based on isoenzyme, RAPD and SSR markers. This study was carried out to assess the utility of SNP markers generated from 3’UTRs for genetic fingerprinting in sweet cherry. A total of 114 sweet cherry germplasm representing advanced selections, commercial cultivars and old cultivars imported from different parts of the world were screened with 7 SSR markers developed from other Prunus species and with 40 SNPs obtained from 3’UTR sequences of Rainier and Bing sweet cherry cultivars. Both types of marker study had 99 accessions in common. The SSR data was used to validate the SNP results. Results showed that the average number of alleles per locus, mean observed heterozygosity, expected heterozygosity and polymorphic information content (PIC) values were higher in SSRs than in SNPs although both set of markers were similar in their grouping of the sweet cherry accessions as shown in the dendrogram. SNPs were able to distinguish sport mutants from their wild type germplasm. For example, ‘Stella’ was separated from ‘Compact Stella’. This demonstrates the greater power of SNPs for discriminating mutants from their original parents than SSRs. In addition, SNP markers confirmed parentage and also determined relationships of the accessions in a manner consistent with their pedigree relationships. We would recommend the use of 3’ UTR SNPs for genetic fingerprinting, parentage verification, gene mapping and study of genetic diversity in sweet cherry.